2023
DOI: 10.1107/s2053229623000062
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structural study on pyridin-3-yl ebselen and its N-methylated tosylate and iodide derivatives

Abstract: The crystal structure of the pyridine-substituted benzisoselenazolinone 2-(pyridin-3-yl)-2,3-dihydro-1,2-benzoselenazol-3-one (C12H8N2OSe, 2), related to the antioxidant ebselen [systematic name: 2-phenyl-1,2-benzoselenazol-3(2H)-one, 1], is characterized by strong intermolecular N...Se(—N) chalcogen bonding, where the N...Se distance of 2.3831 (6) Å is well within the sum of the van der Waals radii for N and Se (3.34 Å). This strong interaction results in significant lengthening of the internal N—Se distance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The crystallographic studies are complemented by DFT calculations of molecular electrostatic potentials. White and co-workers report a study of the pyridin-3-yl derivative of the selenium-containing drug ebselen, 1 (Xu et al, 2023), and its methylpyridinium iodide salt (1-Me + I À ) and tosylate salt (1-Me + CH 3 C 6 H 4 SO 3 À •3H 2 O). The crystal structure of the parent drug (Dupont et al, 1990) and a subsequent charge-density study (Thomas et al, 2015) revealed a short and strong C-Se� � �O C chalcogen bond [Se� � �O = 2.522 (1) A ˚] accompanied by an IR stretching frequency shift [��(CO) ' 71 cm À 1 ].…”
Section: The Virtual Special Issuementioning
confidence: 99%
“…The crystallographic studies are complemented by DFT calculations of molecular electrostatic potentials. White and co-workers report a study of the pyridin-3-yl derivative of the selenium-containing drug ebselen, 1 (Xu et al, 2023), and its methylpyridinium iodide salt (1-Me + I À ) and tosylate salt (1-Me + CH 3 C 6 H 4 SO 3 À •3H 2 O). The crystal structure of the parent drug (Dupont et al, 1990) and a subsequent charge-density study (Thomas et al, 2015) revealed a short and strong C-Se� � �O C chalcogen bond [Se� � �O = 2.522 (1) A ˚] accompanied by an IR stretching frequency shift [��(CO) ' 71 cm À 1 ].…”
Section: The Virtual Special Issuementioning
confidence: 99%
“…We were fortunate that these high-quality co-crystals spanned the range of electron demand ( 1NO 2 · 2b as the electron-poor derivative, 1 · 2b as a neutral derivative, and 1Me · 2b as an electron-rich derivative), giving us the opportunity to examine differences in the experimental charge density in weakly and strongly bonded systems. We were also able to compare these co-crystals with previously reported charge-density studies of single-component crystals of ebselen itself ( 1 ), and a meta -pyridyl derivative ( 1Py ). , The BCPs in the vicinity of the selenium were first inspected, and the values of ρ BCP and ∇ 2 ρ BCP for the Ch-bond (Se···A) and endocyclic Se–N and Se–C bonds are given in Table .…”
Section: Resultsmentioning
confidence: 99%
“…We were also able to compare these co-crystals with previously reported charge-density studies of single-component crystals of ebselen itself (1), and a meta-pyridyl derivative (1Py). 54,55 The BCPs in the vicinity of the selenium were first inspected, and the values of ρ BCP and ∇ 2 ρ BCP for the Ch-bond (Se•••A) and endocyclic Se−N and Se−C bonds are given in Table 4.…”
mentioning
confidence: 99%
“…We were also able to compare these co-crystals with previously reported charge-density studies of single component crystals of ebselen itself (1), and a meta-pyridyl derivative (1Py). 54,55 The BCPs in the vicinity of the selenium were first inspected, and the values of 𝜌 BCP and ∇ 2 𝜌 BCP for the Ch-bond (Se • • • A) and endocyclic Se−N and Se−C bonds are given in table 4. Table 4: QTAIM parameters of Ch-bonded complexes.…”
Section: Resultsmentioning
confidence: 99%